Spatiotemporally Differential Expression of HER (Human Epithelial Growth Factor Receptor)-2 with Sexual Dimorphism in Submandibular Gland of Mice - Pidsaya,Atthapon (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Considering that the submandibular gland (SMG) of postnatal mice performs active cell proliferation, apoptosis and differentiation which are regulated by proto-oncogene products in cancerous cells, the expression and localization of a proto-oncogene product HER (human epidermal growth factor receptor)-2 was examined in SMG of postnatal mice. In Western blot analysis, the expression for HER-2 was high until pre-puberty, and it decreased from puberty to young adult stages with male SMG more dominant. In immunohistochemistry, the immunoreactivity was positive in acinar and ductal cells of newborn SMG with distinct localization at the intercellular apposition sites. The immunoreactivity in acinar cells progressively decreased to negligible levels by pre-pubertal stage, while it remained positive in most ductal cells throughout the postnatal time-course. The immunoreactivity in cells of terminal tubules and intercalated ducts, both of which have a high potential to produce cells, were seen at levels similar to those of more proximal ducts, while the immunoreactivity in ductal basal cells was significantly high, but the granular convoluted tubule cells were seen at negligible levels in male and at faint levels in female. In immuno-electron microscopy of excretory ducts, the immunoreactivity was dominantly localized on the basal infolding membranes as well as vesicles and vacuoles of various sizes, but rarely in Golgi apparatus and mitochondria. The immunoreactivity without association to any membranous structures were also seen, though not numerous. The relation of expression levels of HER-2 in various portions of normal SMG to those in their cancerous ones is briefly discussed.